A Double-Edged Sword: Bandits in the Javanese Revolution: Foes or Friends? - Mukti, Anung Jati Nugraha (Jurnal Sejarah Citra Lekha, 2024)
This research is based on a fundamental question: what was the position of bandits in the Javanese Revolution? Banditry is a social phenomenon connected to crime, the history of the Indonesian Revolution, and the social history of Indonesian society, particularly in Java. This research aims to analyze the social phenomenon of banditry in Java during the post-independence period until the end of the Indonesian Revolution. The research employs historical methods to identify relevant sources. Additionally, researchers incorporate oral interviews with individuals who experienced banditry during the same period. A literature review is also conducted to situate the topic within a complex and nuanced analysis. This research reveals the complex and multifaceted role of bandits in the Javanese Revolution, where they blurred the lines between criminality and heroism. This is further exemplified by the existence of "Revolutionary Bandits" who were utilized by Indonesian military forces in Java as supplementary troops during the revolutionary era.